2021
DOI: 10.1021/acs.organomet.0c00786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnesium and Zinc in Cationic π-Arene and Halobenzene Complexes

Abstract: The reaction of (tBuBDI)­ZnEt with [Ph3C+]­[B­(C6F5)4 −] yielded the cation (tBuBDI)­Zn+ (tBuBDI = CH­[C­(tBu)­N-DIPP]2, DIPP = 2,6-diisopropylphenyl). The cation is sterically too shielded to interact with the ion B­(C6F5)4 – but forms complexes with arenes (benzene, toluene, m-xylene) or halobenzenes (PhX: X = F, Cl, Br, I). Crystal structures of these complexes are compared with those of the corresponding Mg complexes. Although Mg2+ and Zn2+ are of equal size, the Zn···arene and Zn···XPh contacts are genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Like in the previously reported structures of ( Me,DIPP BDI)AlMe 2 and ( Me,DIPP BDI)AlH 2 , [36,37] the (BDI)AlR 2 complexes exhibit Al centres À ] in the polar but weakly coordinating solvent chlorobenzene (Scheme 1). Like observed previously in the syntheses of comparable (BDI)Mg + cations [14][15][16][17] or (BDI)Zn + cations, [18] the colour change from dark orange towards pale yellow or colourless indicated completion of the reaction. Purification of the borate salts, however, was challenging and afforded the laborious development of individual procedures for each individual complex.…”
Section: Complex Syntheses and Structuressupporting
confidence: 82%
See 1 more Smart Citation
“…Like in the previously reported structures of ( Me,DIPP BDI)AlMe 2 and ( Me,DIPP BDI)AlH 2 , [36,37] the (BDI)AlR 2 complexes exhibit Al centres À ] in the polar but weakly coordinating solvent chlorobenzene (Scheme 1). Like observed previously in the syntheses of comparable (BDI)Mg + cations [14][15][16][17] or (BDI)Zn + cations, [18] the colour change from dark orange towards pale yellow or colourless indicated completion of the reaction. Purification of the borate salts, however, was challenging and afforded the laborious development of individual procedures for each individual complex.…”
Section: Complex Syntheses and Structuressupporting
confidence: 82%
“…[10][11][12][13] Our group has been interested in molecule activation with highly Lewis acidic cationic main group metal complexes. [14][15][16][17][18][19] We recently reported that Jordan's cationic β-diketiminate aluminium complex, ( Me,DIPP BDI)AlMe + , can be used as a highly Lewis acidic component in FLP activation of alkynes or CO 2 . [20] Attempts to convert these stoichiometric reactions to a catalytic protocol failed.…”
Section: Introductionmentioning
confidence: 99%
“…TheZ n/Al pair cleaved the CÀFb ond in fluorobenzene instantaneously at room temperature and ( tBu BDI)ZnPh was isolated in 75 %y ield (crystal structure: Figure S56). Ther ecently reported cation ( tBu BDI)Zn + •(p-C 6 H 5 F), in which fluorobenzene binds Zn via its p-system, [49] showed identical reactivity with ( Me BDI)Al, indicating that the Ph ring in ( tBu BDI)ZnPh originates from fluorobenzene and not from benzene.The onward reaction of ( tBu BDI)ZnPh with I 2 is clean and gave ( tBu BDI)ZnI and PhI (Figure S33-S38). Theother product, ( Me BDI)AlF + ,could not be isolated nor observed which is likely due to its very high reactivity.The Al center in the cation ( Me BDI)AlF + would be even more Lewis acidic and reactive than that in hypothetical alumoxane ( Me BDI)AlO [52] and further fluoride abstraction or bond activation reactivity could be anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…Forthe cationic fragment we chose the recently reported ( tBu BDI)Mg + or ( tBu BDI)Zn + entities stabilized by al arge tBu BDI ligand with tBu groups in the backbone. [48,49] This bulky ligand prevents contact between the cation and the B(C 6 F 5 ) 4…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation